FUNCTIONAL ANALYSIS OF MOVIE CHARACTERS: THE CASE OF THE TAG-ALONG - Hsieh, Wei Ting; Chang, Yen Jung (PEOPLE: International Journal of Social Sciences, 2019)
The types of Taiwanese films are becoming more and more abundant, especially those with “thriller” or “horror” elements. In addition to the increase in these types of film production, there are more brilliant box office performances. Therefore, the purpose of this study is to conduct a more in-depth analysis of this type of films. Analyzing the role design and plot direction in the films, so that there is a narrative structure can be referenced in this type of works. This study adopted text analysis, and coupled with the character functions theory proposed by scholar Propp. This study analyzed the functionalities of the main characters in the famous domestic movie “The Tag-Along”. The research results show that there are 6 types of functional characters in “The Tag-Along”: the villain, the helper, the donor, the dispatcher, the hero and the princess. In the 31 character functions listed by Propp, the film contains 18 of them, and these 18 functions are used to describe the story. The film of thriller and horror types are still developing in Taiwan, and the researchers expect to use this research result to find the narrative structure of this type of films. Filmmakers will have a basic structure for reference when creating such movies, and at the same time it extends the other possibilities of this type of films in the development of characters and plots.